The characteristic of GPA and CGPA forecast calculator (GCFC) / Nor Zalina Ismail ...[et al.] - Ismail, Nor Zalina; Abd. Aziz, Muhd. Eizan Shafiq; Razak, Mohd. Rizal; Ramli, Nazirah; Abd. Aziz, Mohd. Norafizal (2016)
Grade Point Average (GPA) and Cumulative Grade Point Average (CGPA) are important mechanisms to assess students' academic performance by many higher academic institutions and some boarding schools in Malaysia. However, the manual calculation process of GPA and CGPA is tedious, time-consuming and sometimes prone to human error. Thus, GPA and CGPA Forecast Calculator (GCFC) is developed to overcome the problem occurred in manual GPA and CGPA calculation and forecasting process. It is developed based on Web Engineering Process Model that is suitable for web application development. GCFC is a convenient web application tool that can ease and speed up the GPA and CGPA calculating and forecasting process. GCFC can be accessed at anywhere and anytime through the internet by using web browsers such as Mozilla Firefox, Goggle Chrome, Internet Explorer and others. GCFC facilitates a user with the "save" button that will save the calculated forecasting GPA and CGPA details into portable document file (PDF) format. Also, GCFC enabled users to print the PDF file for future used. Other special features of GCFC, it gives a freedom to users on deciding the number of subject to be input in the application. This flexibility is useful for future works as it can be expanded to other higher academic institution and boarding schools.